2017
DOI: 10.1016/j.appet.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Binge eating behaviours and food cravings in women with Polycystic Ovary Syndrome

Abstract: Polycystic Ovary Syndrome (PCOS), the most common endocrine condition in women, is often anecdotally associated with binge eating behaviours and food cravings; however there is a paucity of research. This study aimed to report the prevalence of binge eating and food cravings and their relation to obesity risk in women with PCOS. Participants completed an online survey including the Bulimia Investigatory Test, Edinburgh, Food Cravings-Trait Questionnaire and the Three Factor Eating Questionnaire revised-18. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 70 publications
2
56
0
1
Order By: Relevance
“…PCOS is also associated with an increased risk of obstructive sleep apnoea (OSA), placing these women at a further increased risk for long‐term cardio‐metabolic disorders . Obesity commonly underlies these diagnoses, and it is reasonable that each condition contributes to the development of the other . Like PCOS, OSA is associated with depressive disorders; it is plausible that this could contribute to decreased quality of life in PCOS patients .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCOS is also associated with an increased risk of obstructive sleep apnoea (OSA), placing these women at a further increased risk for long‐term cardio‐metabolic disorders . Obesity commonly underlies these diagnoses, and it is reasonable that each condition contributes to the development of the other . Like PCOS, OSA is associated with depressive disorders; it is plausible that this could contribute to decreased quality of life in PCOS patients .…”
Section: Introductionmentioning
confidence: 99%
“…23 Obesity commonly underlies these diagnoses, and it is reasonable that each condition contributes to the development of the other. 23,24 Like PCOS, OSA is associated with depressive disorders; it is plausible that this could contribute to decreased quality of life in PCOS patients. 25 There is a lack of evidence regarding practice guidelines in screening these women for OSA or other sleep disorders, making a better understanding of its prevalence essential.…”
mentioning
confidence: 99%
“…It has been proposed that women with PCOS may have increased risk of EDs, on the basis of several survey-based studies that indicated that women with PCOS had higher scores for abnormal eating behavior or attitude toward eating when compared with women without PCOS (12,16,17). Studies with women who have PCOS reported the prevalence for any EDs in this population ranged from 2.8% to 23.3%, but the methods for diagnosis varied from questionnaires to specialist psychiatric evaluation (18,19).…”
mentioning
confidence: 99%
“…Uncontrolled eating has been shown to correlate positively with BMI (Cornelis et al, 2014), consumption of energy dense foods in middle-aged adults (De Lauzon et al, 2004) and energy intake and central adiposity in mothers (Jaakkola et al, 2013). Larger meal portion sizes in general populations (Spence et al, 2016), binge eating behaviours in women with polycystic ovary syndrome (Jeanes et al, 2017)…”
Section: Literature Reviewmentioning
confidence: 99%
“…The TFEQ-R18 captures tendencies for cognitive restraint, uncontrolled eating and emotional eating. Previous studies have mostly examined each of these tendencies independently and have often focused on specific population categories, such as obese people or women (Anglé et al, 2009;Elfhag & Linné, 2005;Jaakkola, Hakala, Isolauri, Poussa, & Laitinen, 2013;Jeanes et al, 2017;Järvelä-Reijonen et al, 2016;Nevanperä et al, 2012). We argue that going beyond the traditional approach, observing eating behaviour in a more holistic way and in the general population, would enable the development of more effective approaches (such as interventions and products) to overcome eatingrelated problems.…”
Section: Introductionmentioning
confidence: 99%